2023
DOI: 10.1088/1475-7516/2023/02/049
|View full text |Cite
|
Sign up to set email alerts
|

What is flat ΛCDM, and may we choose it?

Abstract: The Universe is neither homogeneous nor isotropic, but it is close enough that we can reasonably approximate it as such on suitably large scales. The inflationary-Λ-Cold Dark Matter (ΛCDM) concordance cosmology builds on these assumptions to describe the origin and evolution of fluctuations. With standard assumptions about stress-energy sources, this system is specified by just seven phenomenological parameters, whose precise relations to underlying fundamental theories are complicated and may depend on detail… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…It has been observed that the curvature term if plugged into the gravitational equations, then it could significantly affect the cosmological parameters [79]. So, the small values of the curvature density parameter obtained from different observational data [73][74][75][76], do not justify the assumption of the spatial flatness of the universe as there is no strong theoretical background available in this regard [80]. In fact, it is very natural to consider the curvature of the universe into the cosmic picture for completeness and then investigate its consequences on the dynamics of the universe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the curvature term if plugged into the gravitational equations, then it could significantly affect the cosmological parameters [79]. So, the small values of the curvature density parameter obtained from different observational data [73][74][75][76], do not justify the assumption of the spatial flatness of the universe as there is no strong theoretical background available in this regard [80]. In fact, it is very natural to consider the curvature of the universe into the cosmic picture for completeness and then investigate its consequences on the dynamics of the universe.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is very natural to consider the curvature of the universe into the cosmic picture for completeness and then investigate its consequences on the dynamics of the universe. Thus, based on the facts that, the non-zero spatial curvature of the universe is indicated by recent observations [69][70][71][72]78]; no solid theoretical background is available to avoid the curvature of the universe [80]; the presence of a spatial curvature of the universe in the gravitational equations could affect the cosmological parameters [79]; one can infer that a thorough cosmological description might be obtained by allowing the spatial curvature in the gravitational equations and test the underlying cosmological scenario with the available data even if the resulting picture becomes complicated. According to the past and current records in the literature, the curvature of our…”
Section: Introductionmentioning
confidence: 99%
“…This means that the flat universe case corresponds to a set of measure zero among all possible spatial geometries. Therefore, an exactly spatially flat Universe has zero probability to be selected among all possible FRLW models (a point that was recently argued in [21]). This raises the question whether ΛCDM with Ω k = 0 should be considered at all.…”
Section: Introductionmentioning
confidence: 95%